2014
DOI: 10.1111/jgs.12994
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Systemic Inflammation and Cognitive Impairment in a Population‐Based Cohort

Abstract: OBJECTIVES Evidence suggests inflammation is associated with cognitive impairment, but previous epidemiological studies have reported conflicting results. DESIGN Prospective population-based cohort. SETTING Epidemiology of Hearing Loss Study participants. PARTICIPANTS Individuals without cognitive impairment in 1998–2000 (N = 2,422; 1,947 with necessary data). MEASUREMENTS Cognitive impairment (Mini-Mental State Examination score <24 or diagnosis of dementia) was ascertained in 1998–2000, 2003–2005, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 56 publications
5
55
0
1
Order By: Relevance
“…74 A doubling of CRP levels has also been implicated in increased risk of hepatocellular carcinoma 75 and cognitive impairment. 76 In the present study, the median CRP level for men with normal BMI was 0.1 mg/L and was more than doubled for men with overweight and obese BMI (1.1 mg/L, and 2.2 mg/L, respectively). Current smoking and hypercholesterolemia were also associated with elevated CRP levels (PD = 53% and 28%, respectively).…”
Section: Discussionsupporting
confidence: 43%
“…74 A doubling of CRP levels has also been implicated in increased risk of hepatocellular carcinoma 75 and cognitive impairment. 76 In the present study, the median CRP level for men with normal BMI was 0.1 mg/L and was more than doubled for men with overweight and obese BMI (1.1 mg/L, and 2.2 mg/L, respectively). Current smoking and hypercholesterolemia were also associated with elevated CRP levels (PD = 53% and 28%, respectively).…”
Section: Discussionsupporting
confidence: 43%
“…In another study, it was reported that a higher intracellular cytokine production of IL-1β and IL-6 by activated monocytes was predictive of lower cognitive performance in working memory in healthy older individuals aged 55-70 years [106]. In a prospective population-based cohort study with data collected over 20 years, it was reported that higher serum CRP and IL-6 were associated with a likelihood of cognitive impairment [107]. These studies indicate that an increased risk of cognitive decline is associated with agerelated inflammatory disorders.…”
Section: Cognitive Functionmentioning
confidence: 94%
“…In model 1, we controlled for age and years of education, well-established confounders for cognitive outcomes, and body mass index (BMI), a confounder for waist circumference. In model 2, we added potential confounders associated with dementia and/or central adiposity [2,612]: cardiovascular (HbA1c; creatinine; total, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) cholesterols; triglycerides; and diastolic and systolic blood pressure), diabetes-related (duration in the Diabetes Registry and diabetes medication status: no medication, insulin only, hypoglycemic medication only, combination of insulin with hypoglycemic medication), APOE ε4 genotype, and inflammation (CRP and IL-6).…”
Section: Methodsmentioning
confidence: 99%